The 21st Century Skills Model of Mathematics Students Today’s Instruction Age - Yanuarto, Wanda Nugroho; Setyaningsih, Eka; Zakaria, Mohamad Ikram (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2025)
Students in today's digital age are required to have 21st-century skills in order to adapt and compete in the real world. However, many students are still not optimally developing their critical thinking and creative problem-solving skills in the context of interdisciplinary learning. This study aims to analyze the influence of exposure to collaborative problem-solving, information and digital literacy, and interactive communication on students' critical thinking and creative problem-solving skills. This study employs a quantitative approach with a cross-sectional survey design. The research subjects are first-year students in the mathematics education program, with a total of 422 respondents. Data were collected using a closed-ended questionnaire based on 21st-century skill indicators and validated by experts. The data analysis technique used is Structural Equation Modeling (SEM) to determine the relationships between variables comprehensively. The results of the study indicate that students' critical thinking and creativity are significantly influenced by interactive communication skills, collaborative problem-solving, and digital information literacy. These findings emphasize the importance of integrating 21st-century skills into mathematics education to support students' readiness to face global challenges. The conclusion of this study is that mastery of collaborative skills, digital literacy, and communication significantly contributes to the development of critical thinking and creative problem-solving among students. The implications of this study suggest the need for curriculum design and teaching strategies that explicitly emphasize the integration of 21st-century skills in the mathematics learning process.